Teaching Causation in Criminal Law: Learning to Think Like Policy Analysts - Brenda Midson (Legal Education Review)
It is generally acknowledged that mooting is an effective way to enhance the teaching of practical skills in legal education as well as to provide an authentic learning experience with links to the real world. However, there are a number of impediments to students participating in mooting; in particular being located off-campus, inexperience and lack of time. It has been suggested that technology may be a means of overcoming these impediments. However the use of technology in mooting has not been tested. This paper will report on a trial of the use of Second Life and Elluminate and videoconferencing as platforms for the conduct of moots. The trials identified limitations in the use of technology for mooting in particularly in relation to the development of advocacy skills. The paper will conclude that these limitations can be overcome by careful consideration of the appropriate technology to be used depending on the context and the objectives to be achieved by the moot. It will also suggest that in order to provide an authentic use of online communication technology in a court setting, the best available technology should be used for the conduct of moot competitions.